Two-step liquid-solid vortex transition with the field along the ab planes in YBa2Cu3O7-δ crystals - Nieva, Gladys (1999)
Fil: Grigera, S.A. Comisión Nacional de Energía Atómica. Instituto Balseiro; Argentina; Universidad Nacional de Cuyo; Argentina